PENERAPAN METODE DEMONSTRASI DENGAN MENGGUNAKAN MEDIA VIDEO TUTORIAL UNTUK MENINGKATKAN AKTIFITAS BELAJAR PADA MATA PELAJARAN PRODUKTIF TEKNIK KOMPUTER JARINGAN SISWA KELAS XI TKJ 1 SMK PKP 2 DKI JAKARTA - Nanang Lidwan; Wawan Ridwan; M. Amas Lahat; M. Mahdi Al Atas (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2020)
This research was conducted to determine the increase in activeness in teaching and learning activities. Students in class XI TKJ 1 SMK PKP 2 Jakarta in practicum activities through video tutorials. This type of research is an action research which is carried out in two cycles, each cycle includes 4 stages of activity, namely: 1) Planning, 2) Implementation of actions, 3) Observation, and 4) Reflection. The research subjects were class XI TKJ 1 in the even semester of SMK PKP 2 Jakarta tajun lessons 2013/2014. The overall results of this study showed an increase in learning activeness, productive subjects TKJ in practicum activities using media, namely video tutorials for improvement in the learning process. From the increase in students who did practicum activities according to the instructions given from 31.81% to 77, 28% this means an increase of 45.47%.